Analysis of Work Discipline, Workload, Compensation, and Their Impact on Employee Performance - Prianto, Lugi; Hadi , Syamsul; Syafwan Lysander, Mohammad Ahyar (Universitas Muhammadiyah Pontianak, 2026)
This study aims to analyze the effect of work discipline, workload, and compensation on the performance of employees of the Dinas Perindustrian dan Perdagangan Daerah Istimewa Yogyakarta (Disperindag DIY). This study uses a quantitative approach based on a questionnaire using a Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree). The technique used was a census, so that the entire population of 69 people became respondents in this study. The data obtained was then processed using SmartPLS4 software applying the Partial Least Square (PLS) and Variance-Based Structural Equation Modeling (SEM) methods. The results revealed that work discipline had a positive and significant effect on employee performance. Workload had a positive but insignificant effect on employee performance. Compensation does not have a significant effect on employee performance. The findings from this study can be a source of theoretical contribution for further development for researchers who want to investigate employee performance. In addition, this study can also be a practical reference that can be used by companies as a basis for developing policies that focus on improving employee performance.